PENYELESAIAN PELANGGARAN KODE ETIK ANGGOTA DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA OLEH MAHKAMAH KEHORMATAN DEWAN - Novita, Nur Qamariah (Katalogis, 2016)
The objectives of the research are to know the completion of ethics code violation of the member of Representatives Council Republic of Indonesia (DPR RI) by Court of Honor Council, case study (Setya Novanto) and to know the provement of violation of ethics code by the member of Representatives Council Republic of Indonesia (DPR RI) in ethic court by court of Honor Council. This research uses normative research method. It elaborates to law approach, conceptual approach, and Setya Novanto’s case. The research analyze juridical qualitatively using deductive-inductive from general description to general based on supporting theory, in order to make easily to interpret in councluding court of Honor Council solves violation of the member of people’representatives council Republic of Indonesia, namely Setya Novanto. Howefer, in completion process, judges of Court of Honor Council (MKD) is a part of fraction or group as same as complainnant (Setya Novanto). Independence of Court of Honor Council (MKD) is not guarantee intervention from others. And, Court of Honor Council (MKD) can not prove on ethichs code violation of the member of People’ Representatives Council (DPR). Because, the objective of provement is that there is ajudgement issuance by Court of Honor Council (MKD) as a formal fullfilled.